Foreing Policy Business USA- Perú: imports of Peruvian Tuna (1952) - Maldonado Félix, Héctor (2009)
The study of foreign policy business is an area that allows us to develop a comparative history and to know how they operate the various branches of government. In 1952 the U.S. Congress debated and rejected a duty on imports of canned tuna which caused a reaction of the Peruvian State that received support from the Department of State and U.S. corporations active in Peru. The study of the U.S. fishing inzdustry and the nascent Peruvian fishing industry may make us understand the various forces that are behind this juncture of Peruvian and American political economy